Retinal structure assessed by OCT as a biomarker of brain development in children born small for gestational age. Issue 9 (9th February 2017) - Pueyo, Victoria; Pérez, Teresa; González, Inmaculada; Altemir, Irene; Gimenez, Galadriel; Prieto, Esther; Paules, Cristina; Oros, Daniel; Lopez-Pison, Javier; Fayed, Nicolás; Garcia-Martí, Gracián; Sanz-Requena, Roberto; et al.
Abstract : Purpose: To identify differences in neuronal tissue from retinal and brain structures in children born small for gestational age (SGA) with no abnormality in neonatal brain ultrasonography and no previous neurological impairment, and to evaluate the relationship between retinal structure and brain changes in school-age children born SGA. Methods: Two cohorts of children were recruited: 25 children born SGA and 25 children born with an appropriate birth weight according to gestational age. All the children underwent an ophthalmic examination, which included retinal imaging using spectral-domain optical coherence tomography, and a brain MRI. MRI images were automatically segmented and global and regional brain volumes were obtained. Results: Although visual function did not differ between both groups, the complex ganglion cell and inner plexiform layers (GCL-IPL) was thinner in SGA children. Total intracranial volume, and global grey and white matter volumes in brain and cerebellum were correlated with birthweight centile, as were certain regional volumes (temporal and parietal lobes, hippocampus and putamen). Abnormal GCL-IPL measurements accurately identified SGA children with the most severe grey and white matter changes in the brain. Conclusions: SGA children, both preterm and term born, showed evidence of structural abnormalities in the retina, which may be an accurate and non-invasive biomarker of neuronal damage in brain tissue.